Vanadium pentoxide effects on stress responses in wine Saccharomyces cerevisiae strain UE-ME3 - Rosado, T (2009)
Vanadium pentoxide mainly used as catalyst in sulphuric acid, maleic anhydride and ceramics industry, is a pollutant watering redistributed around the environment. Research on biological influence of vanadium pentoxide has gained major importance because it exerts toxic effects on a wide variety of biological systems. In this work we intent to evaluate the effects of vanadium pentoxide ranging from 0 to 2 mM in culture media on a wine wild-type Saccharomyces cerevisiae from Alentejo region of Portugal. Our results show that 2.0 mM vanadium pentoxide in culture medium induced a significant increase of malonaldehyde level and Glutathione peroxidase activity, a slightly increase of Catalase A activity as well as a decrease of wet weight and mitochondrial NADH cit c reductase of S. cerevisiae UE-ME3. Also our results show that cycloheximide prevent cell death when cells grows 30 min in presence of 1.5 mMof vanadium pentoxide.